Financial Performance Analysis of PT Wismilak Inti Makmur Related to Its Initial Public Offering Stock Price and Future Prospect (The Indonesian Journal of Business Administration, 2014)
Abstract- This final project will discuss about PT. Wismilak Inti Makmur IPO, the aspects that made Wismilak shares become oversubscribe until 2450%., the decision that made Wismilak for conducting an IPO, Â analyze the performance of Wismilak over the competitors, and to analyze the prospect of Wismilak for the future investment and gives recommendation for investor and Wismilak management to maximize its firm value. Â Keywords: Initial Public Offerings (IPO), Discounted Cash Flow method, Relative Valuation, Capital Structure, Tobacco Industry